Konsep Alam Semesta dalam Perspektif Al-Qur’an dan Hadis (Kajian Tematik) - Naila Zulfa Farrasah; Hardi Setiawan; Alihan Satra (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This article examines the concept of the universe as described in the Qur'an and Hadith and analyzes its relationship with modern science. Using a library research method, this study explores Qur'anic verses and prophetic traditions that describe the creation, structure, and purpose of the universe. The findings reveal that the Qur'an presents the universe as an organized and purposeful creation of Allah SWT, referred to as ayat kauniyah (signs of God's greatness in the natural world). The creation process is described in stages from a unified state (ratq), its separation (fatq), the smoke phase (dukhan), the formation of seven heavens and the earth, to the ongoing expansion of the universe—showing remarkable convergence with modern cosmological theories such as the Big Bang. The study identifies four key wisdoms of creation: a stage for testing human deeds (ibtila'), a facility supporting humanity's stewardship role (taskhir), moral education on discipline and diligence (sunnatullah), and liberation from nihilism. The article concludes that the Qur'an and modern science are not contradictory but complementary, where science explains the mechanism of the universe and the Qur'an provides its meaning and moral direction.